Comparative Study of Drug Addicts Rehabilitation Policy Between Indonesia and Thailand - Bakri, Zulkifli; Said, Muhammad Fachri; Nurhaedah, Nurhaedah (Qawanin Jurnal Ilmu Hukum, 2025)
Abstract: This research aims to conduct a comparative analysis of drug addict rehabilitation policies in Indonesia and Thailand, with a focus on the effectiveness, strategies and approaches implemented. The problem of drug addiction is a serious challenge in both countries, requiring well-structured rehabilitation programs to address the physical, psychological and social aspects of addiction. In Indonesia, rehabilitation efforts have focused more on a combination of medical treatment and social reintegration, with an emphasis on community-based initiatives. In contrast, Thailand has developed a more comprehensive and integrated system, which includes government-regulated treatment, community programs, and alternative punishments for drug offenders. This study analyzes key differences and similarities in the two countries' policies, and evaluates their impact on recovering addicts and broader social outcomes. By comparing the experiences of the two countries, this study aims to provide insights into effective rehabilitation strategies and recommendations for improving drug addiction recovery systems in Southeast Asia. Keywords: Comparative study, drug addiction, rehabilitation, policy analysis Abstrak: Studi ini bertujuan untuk melakukan analisis komparatif terhadap kebijakan rehabilitasi pecandu narkoba di Indonesia dan Thailand, dengan fokus pada efektivitas, strategi, dan pendekatan yang diterapkan. Masalah kecanduan narkoba merupakan tantangan serius di kedua negara, yang memerlukan program rehabilitasi yang terstruktur dengan baik untuk menangani aspek fisik, psikologis, dan sosial dari kecanduan. Di Indonesia, upaya rehabilitasi lebih banyak berfokus pada kombinasi pengobatan medis dan reintegrasi sosial, dengan penekanan pada inisiatif berbasis komunitas. Sebaliknya, Thailand telah mengembangkan sistem yang lebih komprehensif dan terintegrasi, yang mencakup pengobatan yang diatur oleh pemerintah, program-program komunitas, serta alternatif hukuman bagi pelanggar narkoba. Studi ini menganalisis perbedaan dan persamaan kunci dalam kebijakan kedua negara, serta mengevaluasi dampaknya terhadap pemulihan pecandu dan hasil sosial yang lebih luas. Dengan membandingkan pengalaman kedua negara, studi ini bertujuan untuk memberikan wawasan tentang strategi rehabilitasi yang efektif dan rekomendasi untuk meningkatkan sistem pemulihan kecanduan narkoba di Asia Tenggara. Kata kunci: Studi komparatif, kecanduan narkoba, rehabilitasi, analisis kebijakan.